Synonymous nucleotide polymorphisms influence Dombrock blood group protein expression in K562 cells. (11th October 2013) - de, Cécile Durousseau; Silvy, Monique; Halverson, Gregory; Chiaroni, Jacques; Bailly, Pascal; Chapel‐Fernandes, Sylvie
Summary To gain further insight into ART4 (DO) gene alleles (DO*A, DO*JO1, DO*A‐WL, DO*DOYA, DO*B, DO*B‐WL, DO*B‐SH‐Q149K, DO*B‐(WL)‐I175N, DO*HY1, DO*HY2, DO*DOMR) and evaluate the impact of synonymous nucleotide polymorphisms on protein expression and mRNA accumulation of DO*A‐HA, DO*A‐SH and DO*B‐SH alleles, human erythroleukaemic K562 cells were transducted with variant DO‐lentiviral particles and analysed by flow cytometry and quantitative reverse transcription polymerase chain reaction. Monoclonal antibody (MoAb) detection of DO*A‐HA and DO*JO1 transductants was lower than DO*A transductants, while detection of DO*A‐SH, DO*A‐WL and DO*DOYA transductants was higher. Variant DO*B alleles, i.e. DO*B‐SH, DO*B‐WL, DO*HY1, DO*HY2 and DO*DOMR, showed reduced MoAb binding. The unexpected modifications of protein expression of the DO*A‐HA, DO*A‐SH and DO*B‐SH alleles that differ from the DO*A or DO*B alleles by a single synonymous polymorphism were abolished by reversion, thus implying involvement of these polymorphisms. Depending on the Leu208 codon used, detection level ranged from 1 to 4·14. In the variant alleles resulting from single synonymous polymorphism, mRNA accumulation correlated roughly with MoAbs detection levels, suggesting post‐transcriptional regulation. Other than a few reports involving aberrant splicing, the experiments described herein provide the first evidence that synonymous nucleotide polymorphisms can influence Dombrock blood group expression. Such polymorphisms should be taken into account for molecular screening and potential impact on transfusion.